2017
DOI: 10.18203/2349-3291.ijcp20174752
|View full text |Cite
|
Sign up to set email alerts
|

Stress hyperglycemia: clinical profile and outcome in critically ill children

Abstract: INTRODUCTIONStress hyperglycemia(SH) occurs commonly during critical illness in children with previously normal glucose homeostasis. [1][2][3][4] It is often discovered incidentally when routine blood sugar measurements reveal an elevated blood glucose. It is estimated that 49-70% of children with stress hyperglycemia have BG concentrates >150 mg/dl, 20-35% of children have BG > 200 mg/dl. 1-4However the occurrence of blood glucose more than 150 ABSTRACT Background: Stress hyperglycemia (SH) occurs commonly du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Various studies have shown the association of glucose variability with increased mortality. A study done in India showed that patients with isolated blood glucose variability were 5.4 times more likely to die than those with no blood glucose abnormality (8,11) (11).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown the association of glucose variability with increased mortality. A study done in India showed that patients with isolated blood glucose variability were 5.4 times more likely to die than those with no blood glucose abnormality (8,11) (11).…”
Section: Introductionmentioning
confidence: 99%
“…(2,3) Latest studies associate stress hyperglycemia with poor clinical outcome: higher morbidity, complication rate and mortality, supporting the value of stress hyperglycemia as prognosis factor. (4)(5)(6)(7)(8)(9)(10) A complex interplay between hormones and cytokines promoting gluconeogenesis, glycogenolysis and insulin resistance are implicated in the development of stress hyperglycemia. (1)(2)(3)(11)(12)(13)(14)(15)(16) Stress hyperglycemia is commonly identified in children with severe illness and previously normal glucose homeostasis.…”
Section: Introductionmentioning
confidence: 99%